KARAKTERISTIK DIMENSI BERAS LOKAL PROPINSI SUMATERA UTARA DAN KAJIAN KERENTANANNYA TERHADAP Sitophilus oryzae (Coleoptera: Curculionidae) - Hamzah Fansury Nasution; Hendrival Hendrival; Muhammad Muaz Munauwar; Hafifah Hafifiah; Muhammad Yusuf Nurdin (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
The rice weevil, Sitophilus oryzae L. (Coleoptera: Curculionidae) is a major pest and causes damage to rice in storage. This study aimed to study the dimensional characters and determine the susceptibility of rice from germplasm paddy local in Dairi Regency, North Sumatra Province, against S. oryzae during storage. The types of local rice are Sibatubara, Siramos, Sijarum, Siangkat, Si100 hari, Sibosur, Sirukun, Sicantik, and Sigabe. Evaluation susceptibility of rice used the method without choice. The results showed that local rice in Dairi Regency, North Sumatra Province, was grouped into rice long–very long and medium-sized and had different levels of susceptibility against S. oryzae. Rice of Sibatubara, Sijarum, Siramos, and Sicantik was classified as susceptible, while rice Sijarum, Si100 hari, Sirukun, and Siangkat classified as moderate-susceptible. Rice Sigabe were classified moderate against S. oryzae during storage. The susceptibility of rice was influenced by the large number of F1 and short median development time. The damage of higher causes rice classified as susceptible and moderate-susceptible. Dimensions of rice are a source susceptibility rice against S. oryzae.